Acute remote ischemic conditioning enhances (CD3+)- but not (FoxP3+)-T-cell invasion in the tumor center and increases IL 17 and TNF-alpha expression in a murine melanoma model - Rachunek-Medved, Katarzyna; Krauß, Sabrina; Daigeler, Adrien; Adams, Constantin; Eckert, Franziska; Ganser, Katrin; Gonzalez-Menendez, Irene; Quintanilla-Martinez, Leticia; Kolbenschlag, Jonas (Frontiers in Immunology, 2024)
IntroductionHypoxia can drive tumor progression, suppress anti-tumor immunity, and reduce the effectiveness of radiotherapy and chemotherapy. This study aimed to assess the impact of remote ischemic conditioning (RIC) on tumor oxygenation (sO2) and the anti-tumor immune response.Material and methodsFourteen B16-Ova tumor-bearing C57BL/6N mice received six 5-minute RIC cycles, while another fourteen underwent anesthesia only. Pimonidazole was administered 1.5 hours before sacrifice. Blood flow, sO2, and hemoglobin levels were measured in the non-ischemic hind limb and tumor. Tumor hypoxia was assessed using pimonidazole and CA IX immunohistochemistry, and T cell infiltration by CD3 and FoxP3 staining. Serum levels of 23 cytokines were analyzed using a multiplex immunoassay.ResultsIsoflurane anesthesia caused a slight intraindividual increase in blood flow (p = 0.07) and sO2 (p = 0.06) of the hind limb and a sole increase in tumor sO2 (p = 0.035), whereas RIC improved sO2 of the tumor in relation to the hind limb (p=0.03). The median of the tumor oxygen saturation reached 51.4% in the control group and 62.7% in the RIC group (p = 0.09), exhibiting a slight tendency towards better oxygenation in the RIC group. Pimonidazole (p=0.24) and CA IX hypoxia score (p=0.48) did not reveal statistically significant differences between the two groups. In RIC-treated tumors, the number of CD3 (p=0.006), but not FoxP3- positive cells (p = 0.84), in the tumor core was significantly higher compared to the control group. In the RIC group, the mean fluorescence intensity (MFI) of IL-17 was significantly higher (p=0.035), and TNF-α was trend-wise higher (p=0.063) compared to the control group.ConclusionBoth isoflurane anesthesia and RIC have an impact on microcirculation. The application of RIC counteracted some of the effects of isoflurane, primarily in healthy tissue, and led to a significant improvement in relative tumor tissue oxygenation compared to the non-ischemic hind limb. RIC selectively enhanced immune infiltration within the tumor center, probably by previously activated tumor infiltrating T cells, while having no significant impact on T-regulatory cells. RIC appears to impact the cytokine profile, as indicated by elevated MFIs of TNF-α and IL-17.